IMPROVING UNDERSTANDING OF THE DANGERS OF DRUG ABUSE IN ADOLESCENT CHILDREN THROUGH PSYCHOEDUCATIONAL ACTIVITIES - Baliylah Al Imtinan; Farhaniaz Salmaa Reymiza; Katarina Fieschi Stella Arianatagati; Hartati Pragita Thezeus; Dinda Aryani; Ika Yuniar Cahyanti (Universitas Airlangga, 2023)
Introduction: This study aims to determine the effect of psychoeducation regarding drug abuse on participants, namely students of the Muhammadiyah Gayungan Orphanage. Methods: This study used a psychoeducation program in the form of interactive talk shows and psychoeducational video summaries about drug abuse at the Muhammadiyah Gayungan Orphanage. The target participants of this study were 11 children at the Muhammadiyah Gayungan Orphanage. This study used a pretest-posttest design with one group of participants. The data analysis technique used was the independent sample t-test. Results: With a mean difference score of 30.9, providing psychoeducation had a significant effect on increasing adolescent knowledge on drug abuse at Muhammadiyah Gayungan Orphanage (t(11) = 5.49, p = <.001, Cohen's d = 1.65). Conclusion: Psychoeducation regarding drug abuse proved to have a significant effect on the understanding of children at the Muhammadiyah Gayungan Orphanage regarding knowledge of drug abuse.Â KEYWORDS adolescent; drug abuse; psychoeducation.